The Experience of Workplace Emotional Distress and Practice of Self-care in Novice Counsellors - Chen, Cara (Université d'Ottawa / University of Ottawa, 2019)
There is a gap in the literature concerning workplace emotional distress (WED) in novice counsellors. This study explored the lived experience of this phenomenon, as well as common responses used to mitigate it. Three research questions guided this research: (a) what do novice counsellors identify as triggers and predispositions to experiencing emotional distress, (b) what are the perceived consequences of emotional distress on novice counsellors’ clinical work and their work relationships, and (c) what self-care practices do novice counsellors use as protective strategies against emotional distress? Five themes, each with several subthemes, emerged: (a) experiences and feelings associated with client work, which contained four codes; (b) clinician-specific characteristics contributing to WED, which contained three codes; (c) workplace-specific characteristics contributing to WED, which contained five codes; (d) individual actions taken to combat WED, which contained four codes; and (e) policy and training recommendations, which contained three codes. As counsellor distress may cause harm to clients, findings of this research have implications for (a) enhancing the understanding of professional accountability and concerns for public safety, (b) informing decisions of future policy makers, (c) encouraging valuable help seeking or consultation, and (d) de-stigmatize issues of clinician well-being.
Keywords: counselling; novice; burnout; self-care